2022
DOI: 10.31326/jisa.v5i1.1270
|View full text |Cite
|
Sign up to set email alerts
|

Music Genre Recommendations Based on Spectrogram Analysis Using Convolutional Neural Network Algorithm with RESNET-50 and VGG-16 Architecture

Abstract: Recommendations are a very useful tool in many industries. Recommendations provide the best selection of what the user wants and provide satisfaction compared to ordinary searches. In the music industry, recommendations are used to provide songs that have similarities in terms of genre or theme. There are various kinds of genres in the world of music, including pop, classic, reggae and others. With genre, the difference between one song and another can be heard clearly. This genre can be analyzed by spectrogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The time duration of the data affects the accuracy of results obtained, as seen in the comparison of several studies in the duration data comparison (Table 6). Research Time duration Acc % Ahmad [7] 3 seconds 95 Lau [19] 3 seconds 81.73 Zhang [10] 3 seconds 87,4 Vita [9] 30 seconds 58 Purnama [13] 30 seconds 60 Ndou [3] 30…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time duration of the data affects the accuracy of results obtained, as seen in the comparison of several studies in the duration data comparison (Table 6). Research Time duration Acc % Ahmad [7] 3 seconds 95 Lau [19] 3 seconds 81.73 Zhang [10] 3 seconds 87,4 Vita [9] 30 seconds 58 Purnama [13] 30 seconds 60 Ndou [3] 30…”
Section: Resultsmentioning
confidence: 99%
“…Further, the research employed image data resulting from the spectrogram on the GTZAN dataset by comparing two CNN architectures. The results showed that VGG-16 architecture at 20 epochs performed better than the Resnet-50 architecture, with an accuracy of 60% [13].…”
Section: Introductionmentioning
confidence: 98%